Environmental Aspects of V4 Household Consumption - Hošková Elena; Zentková Iveta (Visegrad Journal on Bioeconomy and Sustainable Development)
As the standard of living rises, total household consumption increases. However, in addition to satisfying needs, high consumption also has negative consequences, one of which is environmental pollution. The main objective of this paper is to investigate how household consumption in the V4 countries affects the environment, particularly in terms of waste production. Household consumption is understood through expenditures on food and non-alcoholic beverages, alcoholic beverages, clothing and footwear, and household furniture and equipment. Descriptive statistics and regression analysis are employed for the analysis, using data from Eurostat covering the years 2004-2020. The results indicate that in all V4 countries, as expenditure on food and non-alcoholic beverages increases, household waste production also increases. Other monitored expenditures have varying impacts on waste production across different countries.